Relevansi Pasal 5 Deklarasi Universal Hak Asasi Manusia dan Al-Qur’an; Kontruksi Historis Pidana Islam - Pratama, Brilyan Yudha; Arifin, Tajul; Fauzia, Ine (IAIN Langsa, 2025)
Ideally, Article 5 of the Universal Declaration of Human Rights (UDHR), which prohibits torture, inhuman treatment, or degrading punishment, reflects universal principles that align with the values of justice, dignity protection, and the prohibition of cruel acts in the Qur’an. However, in reality, the implementation of these values often faces challenges both in the global context and in the application of Islamic criminal law, both in classical and contemporary times. This study aims to analyze the relevance of Article 5 of the UDHR with the teachings of the Qur’an and examine the historical construction of Islamic criminal law in implementing these values. This article is classified as qualitative research based on library research, using a normative-historical approach. The methodology employed is content analysis. The study concludes two main points. First, there is significant relevance between Article 5 of the UDHR and the teachings of the Qur’an, particularly in the principles of human dignity protection, justice, and the prohibition of cruel acts. Second, the historical construction of Islamic criminal law shows that these principles have been gradually implemented in various contexts, from the time of the Prophet, the period of the Imams of the madhhab, to the modern era.